Asymptomatic Bacteriuria and Candida Colonization among Pregnant Women in a District Hospital in Eastern Uganda - Bakandonda, Fredrick; Muwanguzi, Shadrack; Nakate, Prossy; Opolot, Ismail; Imongit, Sam; Nnakanwagi, Mariam Mirembe; Nteziyaremye, Julius; Nekaka, Rebecca; Iramiot, Jacob Stanley (Journal of Advances in Medicine and Medical Research, 2019)
Urinary tract infection (UTI) is the most common reason for which antimicrobials are prescribed in pregnancy Worldwide. This study aimed to determine the prevalence of asymptomatic bacteriuria, Candida colonization and antimicrobial susceptibility patterns among pregnant women attending antenatal in a District Hospital in Eastern Uganda. Materials and Methods: A descriptive cross sectional study was conducted in which pregnant mothers who had come for routine antenatal care were counseled and their consents obtained before taking off urine samples for laboratory diagnosis. For those samples found to have pus cells, culture and sensitivity test was done to identify the organisms and determine susceptibility to particular antibiotics and antifungal agents. Results: Gram negative isolates were more sensitive to meropenem (100%), and ciprofloxacin (93.8%) but less sensitive to trimethoprim/sulphurmethoxazole (20%), Ceftazidime (7%), and Cefepime (6%). Gram positive isolates were more sensitive to vancomycin (100%), meropenem (87%) and linezolid (88.1%) but less sensitive to Cefotaxime (31%) and Trimethoprim / sulphurmethoxazole (14%). All bacteria isolated in this study were multi-drug resistant (MDR). All Candida isolates were susceptible to Econazole and Nystatin whereas all isolates were resistant to Griseofulvin. Conclusion: The prevalence of asymptomatic bacteriuria among pregnant women in Butaleja district is high with many of the bacteria isolated exhibiting resistance to the commonly used antibiotics. Antifungal resistance was common in this study.
Keywords: Asymptomatic bacteriuria; Antimicrobial resistance; UTI; Pregnant women